The training value and constraints of established beliefs within teacher training: what is not seen but is perceived in the classroom - Carmen Oliver Vera (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The present article is a reflection on the value of beliefs in both initial and in-service teacher training, and the constraints that they may entail for learning and change. It is framed within the investigation on teachers’ thoughts and focuses on the construction of professional knowledge from the training-innovation relation taking an ecological perspective of knowledge. The concept of belief is defined as an affective and emotional personal dimension, intimately bound to one’s own culture that is manifested in the context in which we are immersed and of which we form part, which in turn exerts an influence on us and on what we do. It is argued that there is a need to take training in this dimension into account in order to promote autonomy as well as professional knowledge self-regulation. Significant constraints which can be overcome are pointed out: not to allow for variation, not to provide arguments, not to promote security to keep on advancing.